A ten-year-surveillance program of zoonotic pathogens in feral pigeons in the City of Madrid (2005–2014): The importance of a systematic pest control. (February 2020) - Perez-Sancho, Marta; García-Seco, Teresa; Porrero, Concepción; García, Nerea; Gomez-Barrero, Susana; Cámara, Jose María; Domínguez, Lucas; Álvarez, Julio
Abstract: Feral pigeons have increased in urban settings worldwide becoming a potential health risk for humans and other animals. Control and surveillance programs are essential to prevent the possible transmission of zoonotic pathogens carried by pigeons. A surveillance program was carried out in Madrid City (Spain) during 2005–2014 to determine the role of urban pigeons as carriers of zoonotic agents comparing these results with studies performed elsewhere in the last fifteen years. A total of 1372 pigeons were randomly captured and tested for detection of Antimicrobial susceptibility and genetic heterogeneity of Campylobacter and Salmonella isolates were determined. During the first phase (August 2005–July 2010), 428 animals were analyzed individually, while in the second period (August 2010–December 2014), 944 pigeons were analyzed in pools ( n  = 2–3 in 2010 and n  = 5–6 in 2013 and 2014). The most prevalent pathogen during the first phase was Campylobacter spp., (6.57%, 95% confidence interval 3.05–12.10%) followed by Salmonella spp. (4.41%, 95% CI: 2.30–7.58%) and C. psittaci (2.56%, 95% CI: 0.70–6.53%)]. The PCR techniques, used during the 2010–2014 phase of the study, confirmed the presence of Campylobacter spp. (prevalence of 0–14.83%) and C. psittaci (0–12, 94%) among pigeons of Madrid. Antimicrobial susceptibility testing suggested low levels of resistance. Presence of zoonotic agents in feral pigeons highlights the importance of surveillance programs on this species, although the relative low prevalence found suggests a limited risk to Public and Animal Health in Madrid. Highlights: 1372 pigeons as zoonotic carriers were assessed in Madrid (Spain) during 2005–2014. Chlamydia psittaci, Camplylobacter spp. and/or Salmonella spp. were investigated. A relative low prevalence was detected suggesting a limited health risk in Madrid Management programs of peridomestic animals should be implemented in urban settings.